Optimization models of the supply of power structures’ organizational units with centralized procurement - Sysoiev, Volodymyr Viktorovych (Центар за издавачку делатност, 2013)
Management of the state power structures’ organizational units for materiel and technical support requires the use of effective tools for supporting decisions, due to the complexity, interdependence, and dynamism of supply in the market economy. The corporate nature of power structures is of particular interest to centralized procurement management, as it provides significant advantages through coordination, eliminating duplication, and economy of scale. This article presents optimization models of the supply of state power structures’ organizational units with centralized procurement, for different levels of simulated materiel and technical support processes. The models allow us to find the most profitable options for state power structures’ organizational supply units in a centre-oriented logistics system in conditions of the changing needs, volume of allocated funds, and logistics costs that accompany the process of supply, by maximizing the provision level of organizational units with necessary material and technical resources for the entire planning period of supply by minimizing the total logistical costs, taking into account the diverse nature and the different priorities of organizational units and material and technical resources.
Keywords: supply; logistics processes; model; optimization; centralized procurement; organizational units of the power structures